2019
DOI: 10.3390/molecules24071363
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib Inhibits Proliferation and Induces Apoptosis of Liver Cancer Cells, but Its Efficacy Is Compromised by Its Activation on PDK1/Akt/mTOR Signaling

Abstract: Ponatinib is a multi-target protein tyrosine kinase inhibitor, and its effects on hepatocellular carcinoma cells have not been previously explored. In the present study, we investigated its effects on hepatocellular carcinoma cell growth and the underlying mechanisms. Toward SK-Hep-1 and SNU-423 cells, ponatinib induces apoptosis by upregulation of cleaved caspase-3 and -7 and promotes cell cycle arrest in the G1 phase by inhibiting CDK4/6/CyclinD1 complex and phosphorylation of retinoblastoma protein. It inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…Our results showed that 9za could retard the cell population at G 0 /G 1 phase at low concentrations (<10 µM). Additionally, cell cycle arrest after 9za treatment could be explained by the decreased levels of CDK4, CDK6 and Cyclin D1, which are consistent with the previous literature (Liu et al, 2019a;Zhang et al, 2018). It is notable that when the concentration was less than or equal to 10 µM, 9za showed a trend of dose-dependent cell cycle arrest in G 0 /G 1 phase.…”
supporting
confidence: 89%
“…Our results showed that 9za could retard the cell population at G 0 /G 1 phase at low concentrations (<10 µM). Additionally, cell cycle arrest after 9za treatment could be explained by the decreased levels of CDK4, CDK6 and Cyclin D1, which are consistent with the previous literature (Liu et al, 2019a;Zhang et al, 2018). It is notable that when the concentration was less than or equal to 10 µM, 9za showed a trend of dose-dependent cell cycle arrest in G 0 /G 1 phase.…”
supporting
confidence: 89%
“…One hypothesis would link necrotic cell death to a blockade of the cell cycle by the TKIs during progression from G1 to S phase. Interestingly, previous in vitro investigation reported a cell cycle arrest in the G1 phase in liver cancer cells treated with ponatinib, and identified that this cell cycle blockade was mediated by a reduction in the function of the CDK4/CDK6/Cyclin D1 complex ( Liu et al., 2019 ). This complex is regulated by the prosurvival PI3K/Akt pathway, known to be impacted by some BCR-ABL TKIs, including ponatinib ( Talbert et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that PDK1 regulates cellular metabolism by activating the AKT/mTOR pathway (30)(31)(32). Adenoviral -PDK1 construct or adenoviral -NC construct was transduced into MC3T3-E1 cells before exposure to dexamethasone.…”
Section: Figure 4 | Upregulation Of Pdk1 Promoted the Osteogenic Abilmentioning
confidence: 99%